Studi Evaluatif Software DCM® untuk Keefektifan Need Asessment Penyusunan Program - Saradewi, Macrina Puspita; anni, catharina tri (Universitas Negeri Semarang, 2016)
This research aims to obtain an overview of the implementation of the SMA needs assessment in Kudus and teacher ratings of the software DCM® BK. This form of research evaluation studies software DCM® used by school counselor in SMA Negeri Kabupaten Kudust by qualitative descriptive research. The study involved a school counselor as the primary data source and school personnel as a secondary data source. The technique of collecting data using interviews, observation, and documentation. Data analysis including data collection, data reduction, data presentation and conclusion. The results of research in the field shows that school counselor SMA Negeri Kabupaten Kudus and already using several types of devices. In analyzing the results of DCM are already using software DCM®, but the operationalize software DCM® still experiencing difficulties, difficulties occurred due to the design of software that still has a weakness or a lack of skills in information technology owned school counselor, it can be concluded that appraisal to software DCM® school counselor are less effective for use in the programming need assessment.